1989
DOI: 10.1002/tea.3660260303
|View full text |Cite
|
Sign up to set email alerts
|

Proportional reasoning: The effect of two context variables, rate type, and problem setting

Abstract: This study investigated the effects of two context variables, ratio type and problem setting, on the performance of seventh-grade students on a qualitative and numerical proportional reasoning test. Six forms of the qualitative and numerical-tests were designed, each form using a single context (one of two settings for each of three ratio types). Different ratio types appear to have a stronger impact on the difficulty of the qualitative and numerical proportional reasoning problems than small differences in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0
4

Year Published

1999
1999
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 8 publications
(3 reference statements)
0
10
0
4
Order By: Relevance
“…Conceptual understanding of physics concepts and information processing is important for students to successfully employ meaningful proportional reasoning strategies during problem solving. Several studies in the past have shown that the subject matter content of problems may influence students' reasoning skills or level of problem‐solving performance (e.g., Heller et al, 1989; Lawton, 1993; Linn, Pulos, & Gans, 1981). The use of proportional reasoning strategy has also been found to depend on the context of the given ratio task (Kuchemann, 1991).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Conceptual understanding of physics concepts and information processing is important for students to successfully employ meaningful proportional reasoning strategies during problem solving. Several studies in the past have shown that the subject matter content of problems may influence students' reasoning skills or level of problem‐solving performance (e.g., Heller et al, 1989; Lawton, 1993; Linn, Pulos, & Gans, 1981). The use of proportional reasoning strategy has also been found to depend on the context of the given ratio task (Kuchemann, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…School science is increasingly permeated by mathematics (Heller, Ahlgren, Post, Behr, & Lesh, 1989), and this suggests a need for the strengthening and integration of mathematics and science instruction. However, more needs to be understood about students' facility with mathematics in their science classes before an integrated mathematics‐ science curriculum can be developed (Fleener, 1993a).…”
mentioning
confidence: 99%
See 3 more Smart Citations